A wide-template and high-accuracy data transfer method for unstructured adjoint-based grid adaptation. Issue 1 (July 2021) - Cui, Pengcheng; Chen, Jiangtao; Li, Bin; Li, Huan; Ma, Mingsheng; Tang, Jing
Abstract: Grid adaptation is an important way to improve the identification of flow field and the accuracy of aerodynamic characteristics. Adjoint-based error estimation and grid adaptation method focuses on improving aerodynamic characteristics by optimizing local grids areas which are more sensitive to output functions. The data transfer between different meshes during the iteration of adjoint-based grid adaptation is the basis of accurate error estimation and grid adaptation. The traditional vertex-based method, however, is not suitable for cell-centred scheme finite volume method. A new wide-template and high-accuracy data transfer method for unstructured adjoint-based grid adaptation is proposed in this paper. Numerical results show that the proposed method is more accurate than traditional node-based method when transferring discontinuous flow field containing shock waves in cell-centred scheme finite volume method, and the accuracy of aerodynamic characteristics is obviously improved after grid adaptation.